Study of incidence and factors associated with postoperative pulmonary complications in patients undergoing abdominal surgery - Ashraf, Nashrah; Zargar, Owais U.; Albina, Ayat; Ahmed, Showkat (International Journal of Research in Medical Sciences, 2024)
Background: Postoperative pulmonary complications are an important cause of increased morbidity and mortality in surgical patients. These complications affect the normal respiratory functions and there are limited studies regarding the contributing factors. The aim of this study was to identify incidence and factors associated with postoperative pulmonary complications in patients undergoing abdominal surgery. Methods: A prospective cross-sectional study was conducted at SKIMS Hospital, Soura. Sample size of 290 patients using systematic random sampling was taken. Variables included sociodemographic, surgical, and anaesthetic factors. Postoperative follow up was done for 7 days. Any respiratory problems were recorded. Both bivariate and multivariate logistic regressions were used for analysis. A p value of <0.05 was considered statistically significant. Results: About 32% of the participants that underwent abdominal surgery developed postoperative pulmonary complications. Age >65 years, duration of surgery >3 hours, preoperative oxygen saturation <94%, and postoperative serum albumin level <3.5 g/dl (p value <0.001) were associated with postoperative pulmonary complications significantly. Conclusions: The incidence of postoperative pulmonary complications after abdominal surgeries was high. Age >65 years, duration of surgery >3 hours, preoperative SpO2% <94%, cigarette smoking, and postoperative serum albumin level <3.5 g/dl were factors strongly associated with postoperative pulmonary complications.